KARAKTERISASI LEMPUNG CENGAR AKTIVASI KOH KALSINASI PADA 300 o C - Laili, Rahmatul; ', Nurhayati; ', Muhdarina (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This research studied about the characteristics of  Cengar’s clay activated with KOH. The clay used was from the village of Lubuk Cengar Jambi Regency Kuantan Singingi. This clay was activated with KOH by impregnation method with variated weights of KOH/Clay i.e 5%, 10%, 15%, 20%, and 25% and the calcination temperature of 300o C. The activated clays were characterized by determining among other types of clay minerals by XRD, Si/Al ratio by gravimetry method,  cation exchange capacity (CEC) by Mehlich method, surface area by blue methylen adsorption, and the site of acid and base clay with alchalimetry and acidimetry method.  The results of XRD showed that mineral kaolinite is lost and replaced by new compounds, namely potassium alumina silicate at KOH concentration of 20% and 25%. The highest Si/Al ratio was at concentration 5% (12.13%) and the lowest at 20% (2,52%). Subsequent observations showed that the highest cation exchange capacity (CEC) was at 5% (349.72 meq/100g) and the lowest was at 10% (91.07 meq/100g). The highest surface area was at 25% (33.273 m2/g) and lowest was at 5% (25,838 m2/g). Acidity and alkalinity in activated clay increase higher than those clays of without activation. The highest acidity was at 10% (1,7550 mmol/g), while the highest alkalinity was at 5% (1,0600 mmol/g).